(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This study evaluates the sensitivity and specificity of ultrasound examination in diagnosing uterine diseases based on morphological analysis. Uterine pathologies frequently present with nonspecific symptoms, especially in early stages, making accurate diagnosis challenging. Ultrasound is a widely used, non-invasive diagnostic method, while morphological analysis remains the gold standard. Determining the diagnostic performance of ultrasound is of significant clinical importance for improving early detection and optimizing patient management.